1999
DOI: 10.1080/13577149977811
|View full text |Cite
|
Sign up to set email alerts
|

Ewing′s Sarcoma of the Head and Neck: A Retrospective Analysis of 24 Cases

Abstract: A bstractIntroduction and pur pose. Primary Ewing's sarcoma arising from the bones of the head and neck region is extremely rare representing only 1± 4% of all Ewing's sarcoma cases. Previous reports suggest a better prognosis for that particular anatomic site. The purpose of this study was to analyze the clinico-epidemiologic characteristics of that rare clinical presentation, as well as its patterns of failure and prognosis following treatment. M ater ials and methods. This study included a retrospective rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 12 publications
7
86
2
2
Order By: Relevance
“…There was a slight male predominance [7] and the majority of patients were less than 30 years of age [6] with a median age of 16 years [7]. Although in some series the prognosis has been suggested to be more favorable for the head and neck region [4,8,18], there have been no large studies of EFT in the sinonasal area specifically and most of the previously reported cases have lacked molecular confirmation. Soft tissue EFT has been reported to have a greater chance of survival for those cases that achieve complete tumor removal prior to chemotherapy [5].…”
Section: Discussionmentioning
confidence: 99%
“…There was a slight male predominance [7] and the majority of patients were less than 30 years of age [6] with a median age of 16 years [7]. Although in some series the prognosis has been suggested to be more favorable for the head and neck region [4,8,18], there have been no large studies of EFT in the sinonasal area specifically and most of the previously reported cases have lacked molecular confirmation. Soft tissue EFT has been reported to have a greater chance of survival for those cases that achieve complete tumor removal prior to chemotherapy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Multimodal treatment yield five year survival rates of about 60% (52-88%) as reviewed in series including atleast one case of Ewings sarcoma / PNET of the head and neck. 6,7 …”
Section: Discussionmentioning
confidence: 99%
“…When long bones are affected, Ewing's sarcoma is typically metadiaphyseal in location [17,18]. Primary Ewing's sarcoma arising from the bones of the head and neck region is extremely rare representing only 1-4% of all Ewing's sarcoma cases [19]. It is the most common malignant bone tumor in children with the peak age being 15 years old.…”
Section: Discussionmentioning
confidence: 99%